Evaluation of SLC16A11 Gene Polymorphisms in Type 2 Diabetes Mellitus Patients - Jassim, Narjes Majed; Abdul-Razaq, Aliaa Saadoon (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The most prevalent form of diabetes, type 2 diabetes mellitus (T2DM), is defined by hyperglycemia in the presence of hyperinsulinemia, which is brought on by insulin resistance and β-cell functional abnormalities of insulin secretion. The work aims to study the association of the SLC16A11 gene with T2DM; besides the 50  healthy individuals who served as the control group, 50  diabetic patients also had their blood drawn. Participants were divided into two groups based on the following criteria: A control group consists of 50 healthy participants between the ages of 20 and 70, while the patient group consists of 50 participants who were diagnosed with diabetes. The patient group had 58% male and 42% female participants, whereas the control group had 52% male and 48% female participants. Despite the fact that many genetic discoveries are relatively recent and have not yet had a significant impact on our understanding of the pathogenesis of diabetes, they have already made a substantial contribution by revealing pathways that could not have been connected to diabetes by presumptive models that already exist. Nevertheless, it's critical to remember that diabetes is probably a far more complex condition than the distinction between T1DM and T2DM suggests.